METACOGNITIVE READING STRATEGIES APPLICATION AMONG HIGH AND LOW PROFICIENT READERS AT PRE-UNIVERSITY LEVEL - Naimah Derin; Suyansah Swanto; Abd Halib Mohd Ali; Wardatul Akmam Din (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In higher education, reading of academic texts is considered as an essential access to scientific knowledge. Therefore, in this survey study will utilize the inventory of Survey on Reading Strategies Questionnaire (SOR) developed by Mokhtari and Sheory. It is explored to identify the two types of readers: high (HPR) and low (LPR) proficient readers at Form Sixth Cenre of Government School in Sabah, Malaysia. There are three major reading strategies: GLOB (Global), SUPP (Support) and PROB (Problem Solving) strategies. This quantitative approach is done by operating the descriptive (mean and standard of deviation) and inferential (Magnitude of effect) statistics. 250 participants from pre-university students randomly selected to respond to the questionnaire The questionnaire finding revealed that PROB strategy was favoured by both readers. To strengthen scrupulous answer, Effect size had given a better interpretation of the finding. The questionnaire provided all reading strategies to be negative effect to the high proficient readers (HPR) yet large positive effect to the low proficient readers (LPR).